Psychometric Properties of the Revised Death Attitude Profile in a Greek Sample of Nurses - Bellali, Thalia; Giannopoulou, Ioanna; Tsourti, Zoi; Malliarou, Maria; Sarafis, Pavlos; Minasidou, Evgenia; Papadatou, Danai (My University, 2018)
Background and Purpose: This study aimed to examine the psychometric properties of the Revised Death Attitude Profile (DAP-R) in a sample of Greek nurses and nursing students. Methods: A convenience sample (n = 934) was used from six National Health System hospitals, and two University Schools of Nursing in central and northern Greece completed the Greek version of the DAP-R (Gr-DAP-R). Results: Principal component analysis with varimax rotation revealed a six-factor solution, including approach acceptance, death avoidance, escape acceptance, neutral acceptance, fear of death, and after death concerns. The internal consistency for each of the subscales ranged from 0.64 to 0.88. Intercorrelations between the Gr-DAP-R subscales supported the relative independence of death attitudes dimensions. Conclusions: The Gr-DAP-R can be used as a research and clinical tool in assessing death attitudes among Greek nurses.
Keywords: Death Attitude Profile-Revised; Exploratory factor analysis; Instrument; Nursing; Principal component analysis; Psychometric properties